In vitro inhibitory effect of Rubraxanthone isolated from Garcinia psrvifolia on platelet- Activating factor receptor binding - Jantan, Ibrahim; Md Pisar, Mazura; Idris, Muhammad Sum; Bakhtiar, M. Taher; Mat Ali, Rasadah (Thieme Verlagsgruppe, 2002)
Rubraxanthone and isocowanol isolated from Garcinia parvifolia Miq. were investigated for their inhibitory effects on platelet-activating factor (PAF) binding to rabbit platelets using 3H-PAF as a ligand. Rubraxanthone showed a strong inhibition with IC 50 value of 18.2 microM. The IC 50 values of macluraxanthone, 6-deoxyjacareubin, 2-(3-methylbut-2-enyl)-1,3,5-trihydroxyxanthone, 2-(3-methylbut-2-enyl)-1,3,5,6-tetrahydroxyxanthone and 1,3,5-trihydroxy-6,6'-dimethylpyrano(2',3':6,7)-4-(1,1-dimethylprop-2-enyl)-xanthone were also determined for comparison. In the course of our study on structure-activity relationship of xanthones, the results revealed that a geranyl group substituted at C-8 was beneficial to the binding while a hydroxylated prenyl group at C-4 resulted in a significant loss in binding to the PAF receptor.